2021
DOI: 10.1016/j.jebo.2021.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Do volatility indices diminish gold's appeal as a safe haven to investors before and during the COVID-19 pandemic?

Abstract: This study addresses the research question of whether volatility indices of different asset classes reduce gold's appeal as a safe-haven asset before and during the COVID-19 pandemic. We use daily data for seven volatility indices and gold prices and apply the suitable nonlinear autoregressive distributed lag method to analyze the data. Our results indicate that during COVID-19, only the negative Eurocurrency volatility has diminished gold prices in the long term, whereas in the short term, the positive gold, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 82 publications
2
9
0
Order By: Relevance
“…In addition to previous study, however they also proved that gold was a safe haven for three other important metals, namely platinum, palladium and silver in this study. Different metal prices volatility were taken into consideration by Tanin et al (2021) who estimated whether different assets volatilities could affect the role of gold as safe-haven, during and before the COVID 19 period. In the long run, adverse Eurocurrency volatility lowered gold prices, but positive silver, gold, emerging market, and financial market volatility reduced gold prices in the short term during COVID-19 period.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to previous study, however they also proved that gold was a safe haven for three other important metals, namely platinum, palladium and silver in this study. Different metal prices volatility were taken into consideration by Tanin et al (2021) who estimated whether different assets volatilities could affect the role of gold as safe-haven, during and before the COVID 19 period. In the long run, adverse Eurocurrency volatility lowered gold prices, but positive silver, gold, emerging market, and financial market volatility reduced gold prices in the short term during COVID-19 period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alternatively, despite an increase of COVID-19 instances, the gold price was quickly rising Atri et al (2021) . Given all of these changes, we believe the COVID-19 outbreak has prompted global investors to look flight-to-safety by purchasing an asset that as a safe-haven asset Tanin et al (2021) .This phenomenon has caught the interest of investors and regulators, resulting in a surge in investment demand for certain commodities. As a result, it is indeed critical for portfolio managers, policymakers and investors to grasp the dynamic relationships between oil, gold, and silver prices ( Abubakari, 2021 ; Alawi, 2021 ; Alsahlawi, 2021 ; Dang et al, 2021 )…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al (2020) reported that gold ETF is a strong safe haven against extreme fall in leading or lagged stock market and against exchange rate risk, similar to the characteristics of gold. Tanin et al (2021) examined the effect of the gold volatility index on gold prices. They found that positive volatility diminishes the price of gold during the Covid 19 period, whereas the impact is negative in the pre covid period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gold is perceived as a safe-haven asset 2 ( Beckmann et al, 2019 ; Harris and Shen, 2017 ; Ji et al, 2020 ; Mensi et al, 2017 ; Tanin et al, 2022 , Tanin et al, 2021b , Tanin et al, 2021c ), and investors buy gold as a hedging instrument ( Singhal et al, 2019 ). Further, gold helps investors diversify their portfolios, thereby minimizing macroeconomic risk ( Agyei-Ampomah et al, 2014 ; Balcilar et al, 2016 ; Baur and Lucey, 2010 ; Baur and McDermott, 2010 ; Beckmann et al, 2019 , Beckmann et al, 2015 ; Bilgin et al, 2018 ; Bouoiyour et al, 2018 ; Gürgün and Ünalmiş, 2014 ; Reboredo, 2013 ).…”
Section: Introductionmentioning
confidence: 99%